2016
DOI: 10.1589/jpts.28.38
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting metabolic syndrome by lifestyle

Abstract: [Purpose] The aim of this study was to explore lifestyle factors in relation to metabolic syndrome so as to be able to utilize the results as baseline data for the furtherance of health-care and medical treatment. [Subjects and Methods] This study was conducted with patients who visited a health care center located in Seoul and had abdominal ultrasonography between 2 March 2013 and 28 February, 2014. Heights, weights, and blood pressures were measured by automatic devices. Three radiologists examined the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Metabolic dysfunctions such as hypertension, obesity and hyperglycemia have been implicated as risk factors for the metabolic syndrome in previous research. 33,34 Obese participants having OR of 15.77 and overweight with OR of 6.55 were at high risk to develop metabolic syndrome in our study. Individuals having age ≥51 years with OR 6.11 had also high risk to develop metabolic syndrome.…”
Section: Discussionmentioning
confidence: 47%
“…Metabolic dysfunctions such as hypertension, obesity and hyperglycemia have been implicated as risk factors for the metabolic syndrome in previous research. 33,34 Obese participants having OR of 15.77 and overweight with OR of 6.55 were at high risk to develop metabolic syndrome in our study. Individuals having age ≥51 years with OR 6.11 had also high risk to develop metabolic syndrome.…”
Section: Discussionmentioning
confidence: 47%
“…20 It is widely recognised that obesity has many negative consequences for health and increases the risk for non-communicable diseases such as cardiovascular diseases and diabetes 21 and the 'metabolic syndrome' . 22 Several dietary factors may have contributed to the high rates of overweight and obesity seen in especially urban women included in the current study. Although quantities of foods consumed were not obtained, women reported that vegetables were often fried in fat/oils and eaten in small portions with large portions of stiff maize-meal porridge (data not shown).…”
Section: Riette Nelmentioning
confidence: 95%
“…Socio-economic growth has served as an advent for commercialization of fast foods and fancy beverages while advancement in technologies have contributed to the switch from active to sedentary lifestyles. Unhealthy diet and sedentary lifestyle are among the main risk factors for metabolic diseases including obesity and type 2 diabetes (T2DM) [1].…”
Section: Introductionmentioning
confidence: 99%